Pro Bono Legal Aid by Advocates: Guarantee of Justice for the Poor - Chairani Azifah (Universitas Negeri Semarang, 2021)
The implementation of legal aid is a manifestation of Indonesia as a legal state that guarantees the human rights of citizens to equality before the law which is guaranteed in the 1945 Constitution. Within the framework of implementing this citizen's human rights, the provision of free legal aid is, among other things, obligated to advocates based on Article 22 Law on advocates and their implementing regulations. From this, two problem formulations were made as follows: What is the juridical review of the provision of pro bono legal aid? And what is the role of advocates in providing pro bono legal aid? This research is based on normative legal research, which is a research conducted by reviewing and analyzing legal materials and legal issues related to the problems studied. The results of the author's discussion found that free legal aid is the right of the poor to obtain the same justice as other communities, so that the protection of their rights is well fulfilled and the principle of equality before the law. Advocates are obliged to provide free legal aid to justice seekers, and to obtain free legal assistance, justice seekers must submit a written application to an advocate organization or legal aid institution.